The unidimensionality of a measurement instrument: A factorial perspective - Burga León, Andrés (2006)
This article explains what we mean by the unidimensionality of a measurement instrument, therefore we present some definitions and  theoretical contributions about this subject. Factor analysis is proposed as one of the many methods for assessing the unidimensionality of a measurement instrument. The use of Pearson correlations matrices on item-level factor analysis is identified as an important problem. Those correlations are problematic because items didn’t carry out the necessary assumptions in order to apply the Pearson correlation: interval-level measurement and normal distribution of the variable. As an alternative we propose and exemplify the use of tetrachoric and polychoric correlations.